Modelling energy efficiency of OR protocols in wireless networks. (10th June 2014) - Mazumdar, Arka Prokash; Waghmare, Anandghan; Sairam, Ashok Singh
Although opportunistic routing (OR) for ad hoc networks have been shown to improve network throughput, energy audit of these protocols have not been done. In this paper, an analytical model to characterise the energy consumption of OR protocols is presented. Total energy consumption is computed taking into account the energy consumed in exchanging control packets, data packet transmission including retransmission and reception. The model considers packet retransmissions that can occur due to network conditions and protocol inaccuracies. The proposed analytical model is used to compute the energy consumption of some well known OR protocols available in literature. The result of the mathematical model is compared with simulation results. The theoretical and experimental results are found to be in conformance.